Vitruvian architecture and ancient rhetoric - Santos, Gilson Charles dos (Revista Archai, 2019)
The aim of this article is to present the essencial analogy between architecture and ancient rhetoric based on the vitruvian treatise De Architectura and the ciceronian De Oratore. The analogy is verified in the definition of artist, of discursive gender and parts in both techniques, and their objectives. For this purpose, I make reference to the sources of Vitruvius De Architecture, namely Varro (in grammar), Lucretius (in philosophy) and Cicero (in rhetorical methods). The analogy with Cicero comprises not only the authority of the ideal architect but also the difference between architecture and other sciences, especially philosophy ”“ object of ciceronian works.